Update in the Peruvian Caponiidae: New records and new species of Nyetnops Platnick & Lise, 2007 (Araneae: Caponiidae) - Villarreal-Blanco, Eduardo; Martínez, Leonel; Eyes-Escalante, Melisa (European Journal of Taxonomy, 2024)
An update on the diversity and distribution of Caponiidae from Peru is presented. New distributional records for Caponina cajabamba Platnick, 1994 are given and the male is described for the first time. Additionally, three new species of the genus Nyetnops Platnick & Lise, 2007 are described: Nyetnops alexanderi Villarreal & Martínez sp. nov. (♂♀), Nyetnops madre Villarreal & Martínez sp. nov. (♂♀) and Nyetnops josei Villarreal & Martínez sp. nov. (♂). The taxonomic key proposed by Sánchez-Ruiz et al. (2020) for Nyetnops is updated to include all the described species as well as the new ones proposed herein. Maps showing the distribution of the records of Caponiidae species in Peru, mainly focused on the genus Nyetnops is included.